2010
DOI: 10.1080/17439760903569154
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral activation interventions for well-being: A meta-analysis

Abstract: One of the most promising ways to increase well-being is to engage in valued and enjoyable activities. Behavioral activation (BA), an intervention approach most commonly associated with the treatment of depression, is consistent with this recommendation and can easily be adapted for non-clinical populations. This study reports on a meta-analysis of randomized controlled studies to examine the effect of BA on well-being. Twenty studies with a total of 1353 participants were included. The pooled effect size (Hed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(157 citation statements)
references
References 58 publications
7
138
0
6
Order By: Relevance
“…The mean effect size for increased life satisfaction was small (d = .16). In comparison, a recentmeta-analysis showed that more traditional, behaviorally-based psychosocial interventions are associated with much larger increases in life satisfaction or subjective wellbeing (mean d = .52; Mazzucchelli, Kane, & Rees, 2010). Furthermore, other positive psychological interventions are associated with moderate to large increases in wellbeing (mean d = .61; Sin & Lyubomirsky, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…The mean effect size for increased life satisfaction was small (d = .16). In comparison, a recentmeta-analysis showed that more traditional, behaviorally-based psychosocial interventions are associated with much larger increases in life satisfaction or subjective wellbeing (mean d = .52; Mazzucchelli, Kane, & Rees, 2010). Furthermore, other positive psychological interventions are associated with moderate to large increases in wellbeing (mean d = .61; Sin & Lyubomirsky, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Because a comprehensive overview of behavioral activation is beyond the scope of the present paper, we refer interested readers to several excellent reviews on behavioral activation's history and current application (Dimidjian et al, 2011;Kanter et al, 2010), empirical evidence (Mazzucchelli et al, 2009;Mazzucchelli, Kane, & Rees, 2010), and assessment strategies ). For the current discussion of behavioral activation and LLD, behavioral activation may be defined as a structured treatment approach that aims (a) to increase engagement in adaptive behaviors and enjoyable activities; (b) to decrease engagement in behaviors that maintain depression or increase the risk of depression; and (c) to target factors that restrict access to reinforcement or maintain aversive control (Dimidjian et al, 2011).…”
Section: Behavioral Models Of Depression: Development and Applicationmentioning
confidence: 99%
“…Behavioral activation interventions have been found to be effective with a broad range of population groups in treating depression (e.g., Cuijpers, Van Straten, & Warmerdam, 2007;Mazzucchelli et al, 2009Mazzucchelli et al, , 2010. Although few studies have examined behavioral activation with older adult populations, such approaches are gaining increasing attention (Dimidjian et al, 2011).…”
Section: Research On Behavioral Activation For Lldmentioning
confidence: 99%
“…Für die Positive Psychologie und die Wirksamkeit der daraus entwickelten Interventionen gibt es mittlerweile eine Vielzahl an empirischen Belegen (Seligman et al 2005;Sin und Lyubomirsky 2009;Mazzucchelli et al 2010). Wissenschaft und Forschung haben damit eine solide empirische Grundlage geschaffen, die in der Praxis des Coachings Anwendung finden kann.…”
Section: Coaching Und Positive Psychologieunclassified